Domestic Violence Experiment in King's County (Brooklyn), New York, 1995-1997 - Davis, Robert C. ([Verlag nicht ermittelbar], 2006)
The researchers sought to add to the incipient literature on randomized studies of batterer treatment, by conducting an experimental study that compared batterers assigned to treatment to batterers assigned to a community service program irrelevant to the problem of violence. The study was conducted using a true experimental design and consisted of 376 spousal assault cases drawn from the Kings County (New York) Criminal Court which were adjudicated between February 19, 1995, and March 1, 1996. Batterers were mandated to attend a 40-hour batterer treatment program or to complete 40 hours of community service. The random assignment was made at sentencing, after all parties (judge, prosecutor, and defense) had agreed that batterer treatment was appropriate, the defendant agreed to treatment and was accepted by the Alternatives to Violence (ATV) program, and the program was available based on the random assignment process. Interviews were also conducted with both the batterer and the victim at sentencing as well as 6 months post-sentence and 12 months post-sentence. These interviews collected data in areas regarding demographics (first interview only), recidivism, beliefs about domestic violence, conflict management strategies, locus of control, and for victims, self esteem. Administrative records were also used to obtain data regarding any new crimes committed.